Perancangan Green Manufacturing Pada Konveksi Arita Industry Semarang, Oox Guitarmaker Ambarawa, Idea Mebel Semarang, PT. Soegiarto Gemilang Tangguh Tegal - Bayu Prestianto; Veronica Kusdiartini (Universitas Katolik Soegijapranata, Semarang, 2022)
Research on green manufacturing was conducted starting with the growth of the industry, which has an impact on environmental pollution. Research on green manufacturing design at Konveksi Arita Industry Semarang, Oox Guitarmaker Ambarawa, Idea Furniture Semarang, PT. Soegiarto Gemilang Tangguh Tegal, aims to know the design of its green manufacturing. The research objectives is to help provide solutions to the managers of the company, especially about Green manufacturing. The data types in this study use primary data with interview and observation data collection methods. The analysis method uses the OECD method of green manufacturing which is used to measure the level of green manufacturing in all four companies. All companies are in the intermediate tier. To achieve a higher level of advanced green manufacturing, of course, each company needs to make a proper green manufacturing design. The design of green manufacturing in each company is done differently according to the conditions of each company. Recommendations that can be delivered that: companies need to streamline the production process in order to minimize the waste produced, start doing 3R (reuse, reduce, recycle) in production activities, using natural and environmentally friendly energy, such as sunlight energy, the use of LED lights, companies need to use environmentally friendly packaging, with the use of ecovalued plastics, in an effort to support the implementation of green manufacturing , then the company needs to conduct socialization and supervision to employees.